2016
DOI: 10.1111/odi.12594
|View full text |Cite
|
Sign up to set email alerts
|

TNFα‐induced IL‐6 and MMP‐9 expression in immortalized ameloblastoma cell line established by hTERT

Abstract: We established an immortalized AM cell line by hTERT transfection. TNF-α-mediated regulation of MMP-9 and IL-6 via NF-κB may play an important role in the pathological behaviour of AMs, such as bone resorption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 53 publications
(61 reference statements)
1
21
0
Order By: Relevance
“… 46 , 47 Matrix metalloproteinases (MMPs), also known as matrixins, are calcium-dependent zinc-containing endopeptidases. 48 The MMPs belong to a larger family of proteases known as the metzincin superfamily. 49 Collectively, these enzymes are capable of degrading all kinds of extracellular matrix proteins, but also can process a number of bioactive molecules.…”
Section: Discussionmentioning
confidence: 99%
“… 46 , 47 Matrix metalloproteinases (MMPs), also known as matrixins, are calcium-dependent zinc-containing endopeptidases. 48 The MMPs belong to a larger family of proteases known as the metzincin superfamily. 49 Collectively, these enzymes are capable of degrading all kinds of extracellular matrix proteins, but also can process a number of bioactive molecules.…”
Section: Discussionmentioning
confidence: 99%
“…MMP series have crucial role in bone destruction, and the difference in expression of these factors could affect the behavior of the tumor, such as invasiveness . Other group reported that TNF‐α induced the expression IL‐6 and MMP‐9 from ameloblastoma cells . However, we have not yet clarified factors that influence the differences in collective cellular invasion in ameloblastoma.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, MMPs have been associated with a wide range of inflammatory disorders [18]. MMP upregulation and downregulation in response to inflammatory mediators, such as cytokines and chemokines has been long demonstrated [19,20], but the existence of feedback mechanisms has been highlighted in recent years [9]. Migration of immune cells by processing extracellular matrix; stimulation and cessation of immune-cell recruitment by processing chemokines and other chemotactic molecules; exacerbation and resolution of inflammatory responses by processing complement, cytokines, and other non-matrix bioactive molecules have been reported [9,12,21,22,23,24,25].…”
Section: Introductionmentioning
confidence: 99%